The two Koreas and the politics of global sport - Bridges, Brian, 1948- (Brill, 2012)
The Two Koreas and the Politics of Global Sport analyses the impact of politics on the development of sport in the two Koreas over six decades and argues that inter-Korean rivalry has significantly influenced sporting ambitions and development.